Composition, structure, and physicochemical characteristics of pigeon pea (Cajanus cajan) starches from Indonesia (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. A’yuni NRL, Marsono Y, Marseno DW, Triwitoyo P. 2021. Composition, structure, and physicochemical characteristics of pigeon pea (Cajanus cajan) starches from Indonesia. Biodiversitas 22: 3430-3439. Information on the characteristics of pigeon pea (Cajanus cajan (L.) Millsp.) starch would provide a scientific basis for developing its application. However, data about characteristics of pigeon pea starch, especially from the Southeast Asia region, has been limited. This study determined the composition, structure, and physicochemical characteristics of pigeon pea starches from three different Indonesian regions, i.e., Bali, Yogyakarta, and West Nusa Tenggara (NTB). We also investigated the potential application of Indonesian pigeon pea starches. Pigeon pea starch was extracted using a wet method, and then pigeon pea starch was characterized. The yield of pigeon pea starches ranged from 29.83-31.68%. Pigeon pea starches showed a significant difference (P
Keywords: Microstructure, physicochemical, pigeon pea, starch